Vaccine Passport and Traveler Behaviors in the New Market of the Domestic and International Tourism Industry Facing the With-Corona Era - Quan, Lanji; Al-Ansi, Amr; Ariza-Montes, Antonio; Arraño-Muñoz, Marcelo; Giorgi, Gabriele; Han, Heesup (Frontiers in Psychology, 2022)
To ensure a smooth and rapid recovery of tourism, countries around the world are stepping up vaccinations against COVID-19. China, in particular has a very high vaccination rate due to its own vaccine production. Following this trend, many countries have started introducing vaccine passports as an alternative solution to verify valid and vaccinated travelers. This study attempted to understand the fundamental perceptions of travelers’ intentions using vaccine passports. A total of 601 samples were investigated and analyzed. As a result, four factors were identified: perceived usefulness, destination trust, risk perception, and perception of incentives. Also, this study performed means comparisons analysis with the major demographic characteristics of respondents. Based on this study, it is expected that the results will contribute to the revival of the travel industry in the future and provide valuable implications for marketing plans to help the travel industry suffer from COVID-19.